Functions of nonsuicidal self-injury (NSSI): Cross-sectional associations with NSSI duration and longitudinal changes over time and following treatment. (30th July 2016) - Victor, Sarah E.; Styer, Denise; Washburn, Jason J.
Abstract: In this study, we sought to clarify if and how the functions of nonsuicidal self-injury (NSSI) relate to duration of NSSI or change over time. To accomplish this aim, we analyzed data obtained from routine clinical evaluations completed within a specialized acute-care treatment program for NSSI. Specifically, we examined how functions of NSSI vary between patients by duration of NSSI, how functions changed within patients over time, and how changes in NSSI functions related to treatment outcomes. Neither internal nor social functions were associated with NSSI duration between patients after controlling for relevant covariates. For patients completing two admissions assessments, internal and social functions decreased similarly over time, although the decrease in internal functions was no longer significant after controlling for decreases in NSSI urges. For patients who completed admissions and discharge assessments, internal and social functions decreased over the course of treatment, with larger decreases in internal functions. Decreases in both types of functions related to improved treatment outcomes. In conclusion, our results suggest that NSSI functions are generally stable across time, although decreases in NSSI functions may relate to clinical improvement. Highlights: We studied nonsuicidal self-injury (NSSI) functions in psychiatric patients. NSSI functions were not associated with NSSI duration between patients. In patients assessed twice, internal and social NSSI functions decreased over time. Decreased NSSI functions during treatment related to improved treatment outcomes.